2021
DOI: 10.1371/journal.pone.0237894
|View full text |Cite
|
Sign up to set email alerts
|

Emerging fungal pathogen of an invasive grass: Implications for competition with native plant species

Abstract: Infectious diseases and invasive species can be strong drivers of biological systems that may interact to shift plant community composition. For example, disease can modify resource competition between invasive and native species. Invasive species tend to interact with a diversity of native species, and it is unclear how native species differ in response to disease-mediated competition with invasive species. Here, we quantified the biomass responses of three native North American grass species (Dichanthelium c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…We expected pathogen transmission from litter to live plants to alter competition between the native and invasive species because pathogen exposure can reduce growth of both species (Kendig et al, 2021;Stricker et al, 2016). However, litter only promoted disease on E. virginicus, and there were no significant effects of disease incidence on E. virginicus establishment or biomass after accounting for litter and planting treatment effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We expected pathogen transmission from litter to live plants to alter competition between the native and invasive species because pathogen exposure can reduce growth of both species (Kendig et al, 2021;Stricker et al, 2016). However, litter only promoted disease on E. virginicus, and there were no significant effects of disease incidence on E. virginicus establishment or biomass after accounting for litter and planting treatment effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, in one greenhouse study, the strength of M. vimineum interspecific competition was not significantly different than the strength of E. virginicus intraspecific competition (Jones, 2009). Bipolaris pathogens infect E. virginicus (Flory et al, 2011;Lane et al, 2020) and can reduce its biomass production (Kendig et al, 2021).…”
Section: Study Systemmentioning
confidence: 99%
“…In contrast, a vascular wilt disease acquired by Ailanthus altissima in its invaded range seemed to have limited effects on most co-occurring species (37, 38). In a greenhouse study, we found that Bipolaris inoculation decreased biomass of E. virginicus , but not two other native species (34). A general rule for how enemy accumulation by invaders affects competitors is therefore difficult.…”
Section: Discussionmentioning
confidence: 90%
“…We estimated small impacts of the invader on the competitor in the absence of disease. Because plants were grown separately prior to planting in the field, we may have missed important competitive interactions among seedlings (34). However, the result that invader-amplified disease negatively impacted the competitor holds regardless of pre-disease competition.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 20 years, leaf spot diseases caused by Bipolaris fungal pathogens that can reduce M. vimineum biomass and seed production have been identified in U.S. M. vimineum populations (Flory et al 2011, Stricker et al 2016. Bipolaris pathogens also infect the native perennial grass E. virginicus (Flory et al 2011, Lane et al 2020) and can reduce its biomass production (Kendig et al 2021).…”
Section: Study Systemmentioning
confidence: 99%